Streaming technologies and their role in modern educational process - Norimova Guljaxon Abduganievna (Genius Journals, 2021)
The article is about the scientific and theoretical basis for the development of students' scientific competencies on the basis of streaming technologies, their scientifically substantiated proposals to improve them on the basis of modern requirements and the combination of quality and effectiveness of education. The organization of streaming technologies in English lessons is based primarily on the classical classified principles of didactics. In this case, the principles of education can be divided into two groups: content-related and organizational-methodological principles of education. Streaming technologies are about students who focus on the comprehensive formation and development of the individual by updating the content, principles, forms and methods of educational activities of students, ensuring their interaction and unity
Keywords: Paradigm; trend; strimming; technology